The disciplinary society and the birth of sociology - Ristić, Dušan (Družboslovne razprave, 2016)
This paper is genealogical research that aims to present one of the historical ways that led to the emergence of sociology as a modern science. We discuss how and why this kind of genealogical research is important for explaining the emergence, transformation and regionalisation of power/knowledge. By following the arguments developed by Michel Foucault, we argue that the disciplinary practices emerging in European societies during the 18th and 19th centuries strongly influenced the upsurge of power/knowledge that would be transformed in sociology. We conclude that the appearance of the institutions - elements of what Foucault called the disciplinary society - led to the rise of new discourses of their legitimisation and to the birth of sociology.
Keywords: Foucault, Michel, 1926-1984; Sociology; Scientific areas; Sociologija; Znanstvene discipline; genealoške raziskave